Shyness's Contribution to Student Engagement in Makassar State University Students - Saputra, Dandi; Alwi, M. Ahkam Alwi; Akmal, Nur (Polteknik Ilmu Pemasyarakatan, 2024)
This study aims to determine the contribution of shyness to student engagement in university students. The respondents in this study were active students from 9 faculties at Makassar State University with a total of 456 people. The measuring instrument used in this study is a student engagement and shyness scales. The data in this study were analyzed using simple linear regression analysis techniques. The results of the data analysis showed a significant value of 0.000, meaning that there is a contribution of shyness to student engagement in UNM students. The r value was -0.430, indicating that shyness has a negative contribution to student engagement with a moderate correlation strength category, and the R Square value was 0.185, meaning that shyness has a contribution of 18.5% to student engagement. The implication of this study is that it can contribute to the development of science related to shyness and student engagement, and can be used as a guide for students and educators in reducing shyness and increasing student engagement.